2012
DOI: 10.1038/oby.2012.188
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Body Fat Classification in the Metabolic Syndrome: Impact on Cardiometabolic Risk Metabotype

Abstract: Objective: Obesity is a key factor in the development of the metabolic syndrome (MetS), which is associated with increased cardiometabolic risk. We investigated whether obesity classification by BMI and body fat percentage (BF%) influences cardiometabolic profile and dietary responsiveness in 486 MetS subjects (LIPGENE dietary intervention study). Design and Methods: Anthropometric measures, markers of inflammation and glucose metabolism, lipid profiles, adhesion molecules, and hemostatic factors were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
0
33
0
1
Order By: Relevance
“…Furthermore, it was found that there is a major risk for aggregation between hypertension and obesity. 6 In an epidemiological prospective study, the relationship between BMI and mortality from CVD was reported, yet it was reduced or it disappeared after adjustment for lipid profile, blood pressure and diabetes variables, suggesting that these play a significant role in the development of CVD when related to obesity. Previous studies also showed that high blood pressure was associated with obesity, 9 increase in body fat 22 and higher BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was found that there is a major risk for aggregation between hypertension and obesity. 6 In an epidemiological prospective study, the relationship between BMI and mortality from CVD was reported, yet it was reduced or it disappeared after adjustment for lipid profile, blood pressure and diabetes variables, suggesting that these play a significant role in the development of CVD when related to obesity. Previous studies also showed that high blood pressure was associated with obesity, 9 increase in body fat 22 and higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unfavorable lipid profile is also highly prevalent among the elderly, 4 with 35% of men and 60% of women. 6 Results from the Framingham Heart Study showed that obese adults with body mass index (BMI) greater or equal to 30 kg/m 2 had a life expectancy of 6-7 years less compared with individuals with normal BMI. 6 Results from the Framingham Heart Study showed that obese adults with body mass index (BMI) greater or equal to 30 kg/m 2 had a life expectancy of 6-7 years less compared with individuals with normal BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, whether obesity in its various forms has the same state of subclinical inflammation is still a matter of debate. Recently, in fasting state, we have observed that metabolically abnormal individuals displayed a more proinflammatory (higher hs-CRP and leptin), prothrombotic (higher plasminogen activator inhibitor-1 (PAI-1)), and proatherogenic (higher leptin/adiponectin ratio) metabolic profile relative to the metabolically healthy group [30]. In this study, as expected, obese, metabolically abnormal subjects displayed a higher hs-CRP postprandial response compared with the subgroup of normal, overweight and obese metabolically healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is also associated with hypertrophic adipocytes that secrete inflammatory cytokines and chemokines, which promote infiltration of proinflammatory macrophages into white adipose tissue (WAT) (Zeyda and Stulnig, 2007). Proinflammatory effects of certain adipokines cause dysregulation of lipid and energy metabolism (Bae et al, 2014(Bae et al, , 2015Feingold et al, 1992;Kawakami et al, 1987;Sakamoto et al, 2013) and development of metabolic disorders, such as insulin resistance and atherosclerosis (Phillips et al, 2013). There is renewed interest in understanding the fundamental mechanisms that link inflammation and metabolic dysregulation in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%